EVALUASI DAN PENINGKATAN KINERJA PELAYANAN RUANG TUNGGU KEBERANGKATAN BANDARA INTERNASIONAL AHMAD YANI SEMARANG - Muhammad Khalif; Mardonas Mardonas; Bambang Pudjiastuti; Ismiyati Ismiyati (Departemen Teknik Sipil, Fakultas Teknik Universitas Diponegoro, 2013)
Ahmad Yani International Airport in Semarang is one of the biggest airports in Central Java. Ahmad Yani International Airport in Semarang connecting various cities in Indonesia, especially Jakarta and Surabaya as well as the city to city which is on the island of Borneo. The number of passengers in the year 2010 amounted to 2,017,952 passengers. To get the service aircraft needs to be provided for the passenger waiting area before departure. The problems that arise are less than the requirement for a seat on the airport passenger terminal, in particular the departure lounge during peak hours and the occurrence of delayed. Data processing using queuing theory that the intensity obtained on 24th November 2012, at ρ = 0.9 <1 and 25th November 2012 ρ = 1.09 > 1 and obtained the optimum amount of seating as many as 269 on 24th November 2012 and 322 on 25th November 2012 at a cost of airport tax of analysis is Rp 38,000.00 while the number of seats as many as 315 existing condition with the existing airport tax fee is Rp 35,000.00.